Inter-calibration of Infrared Channels of Geostationary Meteorological Satellite Imagers - Rublev, Alexey N.; Gorbarenko, Ekaterina V.; Golomolzin, Vladimir V.; Borisov, Evgeny Y.; Kiseleva, Julia V.; Gektin, Yuriy M.; Zaitsev, Alexander A. (Frontiers in Environmental Science, 2018)
This article examines a method of inter-calibration for MSU-GS imager of the Russian Geostationary Earth Orbit (GEO) satellite Elektro-L No. 2. Since the launch (December 11, 2015), the satellite's radiation cooler has been operating in an abnormal mode, so the calibration of the IR channels of the MSU-GS imager differed from that pre-flight and, in general, could have a daily variability. To ensure the satellite’s further operation in orbit, it was necessary to calibrate imager channels at a frequency that would allow to identify daily calibration course to detect and compensate its sources. In order to do this, we have developed a special method of GEO-GEO inter-calibration. The calibration of MSU-GS was performed using SEVIRI imager installed on the GEO satellite Meteosat-10. SEVIRI was chosen as a reference instrument because its spectral channels are similar to those of MSU-GS. The MSU-GS was calibrated according to the regressions calculated from the simultaneously images of the field of regard selected between the sub-satellite points. The dynamic brightness temperature (BT) range was determined by deep convective clouds in high troposphere and warm ocean surface. Using the proposed method of inter-calibration, it was possible to confirm the absence of a significant daily variation of the calibration since November 2017. The amplitude of the variation smoothly increases from ~0.2K at high (~ 300K) BTs to ~ 1.0K when the temperature decreased to 200K. These estimates allow the use of the Fourier spectrometer IKFS 2 installed on the Russian Low-Earth-Orbit (LEO) satellite Meteor-M No. 2 to verify the developed GEO-GEO scheme of inter-calibration. Despite the specifics of the situation on board Elektro-L No. 2, the proposed method of GEO-GEO inter-calibration can be applied to radiometers of other neighboring satellites that differ in SSP and spatial resolution.